The Effect of COVID-19 Pandemic on Body Weight, Physical Activity and Lifestyle of UniKL RCMP Students - Nor Shafiqah Baso Sultan Bakri; Aina Amanina Abdul Jalil; Nor Safwan Hadi Nor Afendi (Asian Journal of Medicine & Health Sciences, 2022)
Background: Coronavirus disease (COVID-19) is an infectious disease which emerged in December 2019 from Wuhan, China and has since spread worldwide. In March 2020, the World Health Organisation (WHO) declared the outbreak as pandemic. Malaysian government has implemented a Movement Controlled Order (MCO) to combat this pandemic which has limited outdoor activities and affected public’s social lives, physical activities and eating habits as they were prohibited from leaving their house unless necessary. This study was conducted to identify the effects of COVID-19 pandemic on body weight, physical activity and lifestyle among Universiti Kuala Lumpur Royal College of Medicine Perak (UniKL RCMP) students. Methods: A cross-sectional study was conducted among 330 UniKL RCMP students by distributing online questionnaires via various platforms. Descriptive data was presented as frequency and percentages (%) or means and standard deviations of means. The association between body mass index (BMI) and physical activity classification as well as BMI and lifestyle classification were analysed using Chi-square test. Results: The percentage of students who were inactive rose during COVID-19 pandemic while the percentage of students who were highly and moderately active reduced. During pandemic, majority (80.6%) of the students had poor dietary habits. This study has also proven that the pandemic has negatively impacted the students, as 56.4% of them reported an increase in body weight. There was a significant association between BMI category and physical active classification before and during pandemic (p= 0.20, p